PERAN BUDAYA ORGANISASI TERHADAP KINERJA DOSEN: KAJIAN LITERATUR REVIEW - Yanti, Dyah Agustin Widhi (Magister Manajemen Universitas Wisnuwardhana, 2020)
The hassle of higher training in Indonesia in the strategic layout of the Ministry of Research, Technology and Higher Education (2015) states that the great of higher training is still rather low in the context of greater training and study packages indicated through the majority of universities only being permitted C and solely a few getting accreditation A. or B. Previous literature reviews have explored the relationship between organizational subculture and lecturer performance. The cause of this scope overview is to map out current research that examine the have an impact on of organizational subculture on lecturer performance. The results of the scoping review exhibit that most research recognize organizational culture as influencing lecturer performance. The outcomes of research carried out by Sambasivan and Johari (2003), Sangadji and Sopiah (2013), Dirwan (2015), Handoko, et al. (2010).